2023
DOI: 10.1101/2023.02.16.528808
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of the acute effects of 2C-B vs psilocybin on subjective experience, mood and cognition

Abstract: 2,5-dimethoxy-4-bromophenethylamine (2C-B) is a hallucinogenic phenethylamine derived from mescaline. Observational and preclinical data have suggested it to be capable of producing both subjective and emotional effects on par with other classical psychedelics and entactogens. Whereas it is the most prevalently used novel serotonergic hallucinogen to date, it′s acute effects and distinctions from classical progenitors have yet to be characterised in a controlled study. We assessed for the first time the immedi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 109 publications
(145 reference statements)
1
3
0
Order By: Relevance
“…The time course of the subjective quality of the psychedelic experience was assessed by tracking mean scores on ASC questions during the dosing session ( Figure 3 ). This time course was comparable to previous studies with psilocybin 55 , peaking about 2 hours after psilocybin administration ( Figure 3A ). Participants administered higher doses of midazolam did not experience a reduction in the magnitude or the duration of elevated ASC scores.…”
Section: Resultssupporting
confidence: 90%
“…The time course of the subjective quality of the psychedelic experience was assessed by tracking mean scores on ASC questions during the dosing session ( Figure 3 ). This time course was comparable to previous studies with psilocybin 55 , peaking about 2 hours after psilocybin administration ( Figure 3A ). Participants administered higher doses of midazolam did not experience a reduction in the magnitude or the duration of elevated ASC scores.…”
Section: Resultssupporting
confidence: 90%
“…measures; 1 negative acute finding was excluded because it followed intravenous psilocybin administration thereby making dosage comparison with oral administration meaningless; and 18 neutral and 7 negative acute findings were excluded because they lacked adequate dosage information. Overall, the excluded acute findings were primarily negative (56%) and neutral (41%) as opposed to positive (4%), thus demonstrating a pattern of outcomes that is consistent with those included in the figure . Effect sizes were reported in four (10%) of the included publications (Mallaroni et al, 2023;Mason et al, 2021;Prochazkova et al, 2018;Vollenweider et al, 2007). Mallaroni et al (2023) reported the following significant negative outcomes with large effect sizes during the acute phase following a 15-mg psilocybin macrodose: increased reaction time on the Tower of London Test 2021) reported significant impairments with large effect sizes during the acute phase following a 0.17 mg/kg psilocybin macrodose for the fluency measure (d = 0.80) on the Alternate Uses Task, and the fluency (d = 0.84) and convergent (d = 0.85) measures on the Picture Concept Task, and significant impairment with a medium effect size for the originality measure (d = 0.65) on the Picture Concept Task (all measures of creativity).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Overall, the excluded acute findings were primarily negative (56%) and neutral (41%) as opposed to positive (4%), thus demonstrating a pattern of outcomes that is consistent with those included in the figure . Effect sizes were reported in four (10%) of the included publications (Mallaroni et al, 2023;Mason et al, 2021;Prochazkova et al, 2018;Vollenweider et al, 2007). Mallaroni et al (2023) reported the following significant negative outcomes with large effect sizes during the acute phase following a 15-mg psilocybin macrodose: increased reaction time on the Tower of London Test 2021) reported significant impairments with large effect sizes during the acute phase following a 0.17 mg/kg psilocybin macrodose for the fluency measure (d = 0.80) on the Alternate Uses Task, and the fluency (d = 0.84) and convergent (d = 0.85) measures on the Picture Concept Task, and significant impairment with a medium effect size for the originality measure (d = 0.65) on the Picture Concept Task (all measures of creativity). The same study found that at 7-day follow-up, psilocybin resulted in significant impairment with a medium effect size for the convergent measure on the Picture Concept Task (d = 0.60) and significant enhancement with a medium effect size for the novel measure on the Alternate Uses Task (d = 0.52).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation